Complete mitogenome of the dog cucumber tapeworm Dipylidium caninum (Cestoda, Dilepididae) from Southwest China. Issue 2 (3rd July 2019) - Xie, Yue; Liu, Yunjian; Gu, Xiaobin; Meng, Xiaduo; Wang, Lu; Li, Yingxin; Zhou, Xuan; Zheng, Youle; Zuo, Zhicai; Yang, Guangyou
Abstract: The cucumber tapeworm Dipylidium caninum (Cestoda, Dilepididae) is a common intestinal parasite of dogs and cats and can cause dipylidiasis in humans, especially in infants and children. In this study, the complete mitogenome of this tapeworm was sequenced using next-generation sequencing technology. The entire genome was 14, 226 bp in size and encoded 36 genes, including 12 protein-coding genes, 22 transfer RNA genes, and 2 ribosomal RNA genes. The phylogeny revealed that D. caninum grouped with other species from the order Cyclophyllidea and separated from species of Pseudophyllidea. Within the Dipylidiidae, both dog-originated D. caninum were phylogenetic distinctiveness from cat-originated D. caninum, suggesting that D. caninum may represent a species complex. Altogether, the complete mitogenome of D. caninum sequenced here should contribute to a better understanding of the phylogenetic and taxonomic placement of this species.